1990
DOI: 10.1007/bf02333864
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-like headache and head injury: case report

Abstract: This appears to be the first report of cluster-like headache secondary to post-traumatic subdural hematoma. A 39 year old man consulted us for cluster-like headáche on the right side following an injury to the right frontotemporal region some 45 days before. A CT scan revealed a chronic subdural hematoma in the right frontotemporal region. We discuss the possible relationship between the head injury and the headache and suggest the value of CT scanning in patients with cluster headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…The only CH case secondary to head trauma that fulfills the 1988 International Headache Society (IHS) criteria 5 was described by Turkewitz et al, but the follow‐up was too short for any conclusive evidence on the headache's temporal pattern 6 . Other authors reported CH onset following head trauma, but in these cases the headache did not fulfill the 1988 IHS criteria for post‐traumatic headache 7‐9 . In the International Classification of Headache Disorders, 2nd edition (ICHD‐II), post‐traumatic CH is coded to group 5 (“Headache attributed to head and/or neck trauma”).…”
Section: Introductionmentioning
confidence: 99%
“…The only CH case secondary to head trauma that fulfills the 1988 International Headache Society (IHS) criteria 5 was described by Turkewitz et al, but the follow‐up was too short for any conclusive evidence on the headache's temporal pattern 6 . Other authors reported CH onset following head trauma, but in these cases the headache did not fulfill the 1988 IHS criteria for post‐traumatic headache 7‐9 . In the International Classification of Headache Disorders, 2nd edition (ICHD‐II), post‐traumatic CH is coded to group 5 (“Headache attributed to head and/or neck trauma”).…”
Section: Introductionmentioning
confidence: 99%
“…If we keep these ICHD-II criteria in mind, then the only sure case of post-traumatic CH reported in the literature is that described by Turkewitz et al [28•], who presented a patient in whom CH occurred 6 days after head trauma. Strictly speaking, neither the four patients who developed CH after a few weeks described by Reik [25], nor the patient in whom CH appeared only after 45 days described by Formisano et al [27] can be ascribed to this category. Among the cases reported in the literature with CH onset after eye enucleation, the one with the shortest latency between the two events is the patient who began to suffer from CH 3 weeks after surgery (and nearly 8 months after head trauma) described by Evers et al [30].…”
Section: Post-traumatic Cluster Headachementioning
confidence: 93%
“…In 1990, Formisano et al [27] described a 39-year-old patient who developed a right-sided cluster-like headache 45 days after a head trauma in the right frontotemporal region, with subsequent chronic subdural hematoma.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The durations of the headaches at the time of writing were 2, 4.5, 8, and 46 years. In 1990, Formisano et al [24] reported cluster-like headaches after a post-traumatic subdural hematoma. The headaches occurred approximately 6 weeks after the injury, described as minor without loss of consciousness.…”
Section: Head Traumamentioning
confidence: 99%